CFD parametric study of the influence of number and arrangement of meat carcasses in the thermal performance of refrigeration rooms - Bastos, Emanuel da Costa (2014)
This paper describes the numerical results of a CFD parametric studies of the influence on the thermal performance of a cold room by (1) the number and arrangement (n = 6, 9, 18, 30 and 40) of meat carcasses hanging in an airway; (2) the air temperature in the antechamber (T = 5ºC; 14ºC and 22ºC); and of (3) opening the door of the cold room. The case studies were tested in a real facility. A steady state 3D CFD model of the cold room is developed, allowing the detailed evaluation of the airflow and heat transfer for each case study. The thermal conduction within the meat carcasses is also predicted. The numerical predictions show that the average air temperature inside the cold room as well as the average carcass temperatures increase with the number of products and depend on the arrangement of the carcasses in the airway. A minimum space between carcasses is required to improve the refrigeration process. Similarly, the heat load of the cold room increases with the air temperature of the antechamber and when the door of the cold room is opened. The carcasses temperature profile becomes less uniform when the door is opened, being the temperature of carcasses located near the door strongly affected. These parametric studies allow to evaluate details of the air flow and heat transfer by convection and conduction inside goods that can contribute to the design of cold rooms in order to focus on the improvement of thermal performance and consequently of food safety and energy efficiency.